2015
DOI: 10.1532/hsf98.20121101
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Outcomes Associated with Coronary Artery Bypass Graft Surgery and Recent Clopidogrel Exposure

Abstract: Clopidogrel exposure within 5 days of CABG is associated with an increased risk of major bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The overall mortality rate in those who took clopidogrel up to the time of surgery was also higher. These findings were reflected in a retrospective analysis of CABG patients ( n = 715): a significant association was observed between bleeding and clopidogrel exposure within 5 days before surgery 315 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The overall mortality rate in those who took clopidogrel up to the time of surgery was also higher. These findings were reflected in a retrospective analysis of CABG patients ( n = 715): a significant association was observed between bleeding and clopidogrel exposure within 5 days before surgery 315 …”
Section: Discussionmentioning
confidence: 89%
“…These findings were reflected in a retrospective analysis of CABG patients (n ¼ 715): a significant association was observed between bleeding and clopidogrel exposure within 5 days before surgery. 315 A meta-analysis of 12 studies reported that continuing antiplatelet therapy (aspirin and clopidogrel) until the time of cardiac surgery was associated with increased blood loss, but carried a low risk of surgical re-exploration for bleeding. 316 The authors concluded that in patients at a high risk of stent thrombosis, this may be acceptable.…”
Section: Evidence Summarymentioning
confidence: 99%
“…The findings of RCTs have been reflected in a recent retrospective analysis of CABG patients (n ¼ 715): a significant association was observed between bleeding and clopidogrel exposure within 5 days before surgery. 196 A recent meta-analysis of 12 studies reported that continuing antiplatelet therapy (aspirin, clopidogrel) until the time of cardiac surgery was associated with increased blood loss, but carried a low risk of surgical re-exploration for bleeding. 197 The authors concluded that in patients at a high risk of stent thrombosis, this may be acceptable.…”
Section: Clopidogrelmentioning
confidence: 99%